2021
DOI: 10.1017/s0021932021000353
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health knowledge and behaviour of adolescent boys and girls aged 10–19 years in western Kenya: evidence from a cross-sectional pilot survey

Abstract: This paper reports findings of a pilot survey of adolescent sexual and reproductive health (ASRH) knowledge and behaviour in Homabay County of western Kenya. The study was based on a cross-sectional survey of 523 male and female adolescents aged 10–19 years from 32 Community Health Units (CHUs). Bivariate analysis of gender differences and associations between ASRH knowledge and behaviour was followed with two-level logistic regression analysis of predictors of ASRH behaviour (sexual activity, unprotected sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This indicates more media exposure and better educational attainment would lead to better knowledge on pregnancy prevention, which mediates less risky sexual behavior as well as more contraceptive use, which in turn leads to reducing early fertility. Previous studies showed that having better knowledge on sexual and reproductive health would reduce risk sexual behavior among adolescent women (Champion et al, 2013;Finlay et al, 2020;Magadi et al, 2022). Additionally, studies in sub-Saharan Africa that included media exposure as explanatory variables show association between media exposure and sexual behaviors and outcome on early fertility (Ahinkorah, Ameyaw, et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…This indicates more media exposure and better educational attainment would lead to better knowledge on pregnancy prevention, which mediates less risky sexual behavior as well as more contraceptive use, which in turn leads to reducing early fertility. Previous studies showed that having better knowledge on sexual and reproductive health would reduce risk sexual behavior among adolescent women (Champion et al, 2013;Finlay et al, 2020;Magadi et al, 2022). Additionally, studies in sub-Saharan Africa that included media exposure as explanatory variables show association between media exposure and sexual behaviors and outcome on early fertility (Ahinkorah, Ameyaw, et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Second, male adolescents (21%) are more aware of using condoms than female adolescents (7%). Third, more male adolescents (17%) use condoms during sexual intercourse than female adolescents (3%) [31]. Meanwhile, 11.0% of male adolescents and only 5.7% of female adolescents have sexual intercourse.…”
Section: Discussionmentioning
confidence: 98%
“…[38][39][40] The fear of the sexual behavior consequences appears to encourage female adolescents to have more information on reproductive health as well as contraception. 40,41 A study in Kenya found that female adolescents were more likely to find more information about contraceptive methods and reproductive health to avoid the risks of an unwanted pregnancy. 37 Another study in Italy stated that the differences related to sex differences are possibly due to adverse effects of the prevention services design and health promotion which has been traditionally more focused on women.…”
Section: Discussionmentioning
confidence: 99%